2016
DOI: 10.1007/s00432-016-2185-5
|View full text |Cite
|
Sign up to set email alerts
|

Altered CXCL12 expression reveals a dual role of CXCR4 in osteosarcoma primary tumor growth and metastasis

Abstract: Higher abundance of CXCR4 possibly contributed to increased local retention of tumor cells by bone marrow-derived CXCL12, reflected in the increased primary tumor growth and decreased number of lung metastases in P2G and CXCL12-KDEL groups. Higher percentage of CXCR4-expressing lung metastatic cells compared to the corresponding primary tumors point to important functions of the CXCL12/CXCR4 axis in late steps of metastasis. In conclusion, based on the here reported results, local treatment of lung metastases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…Considering the similarity between molecular functions and cell components of hub IRGs, and through the ranking of semantic similarity, we discovered that CCR5, CXCL12 and CXCR4 are the most closely related genes. CCR5, CXCL12 and CXCR4 genes encode chemokine receptors or ligands, which plays a vital part role in the initiation and growth of OS 29 , 41 , 42 . These findings further support the reliability of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the similarity between molecular functions and cell components of hub IRGs, and through the ranking of semantic similarity, we discovered that CCR5, CXCL12 and CXCR4 are the most closely related genes. CCR5, CXCL12 and CXCR4 genes encode chemokine receptors or ligands, which plays a vital part role in the initiation and growth of OS 29 , 41 , 42 . These findings further support the reliability of our study.…”
Section: Discussionmentioning
confidence: 99%
“…CXCR4 is the receptor of chemokine SDF-1, which regulates cell migration and involved in cancer progress and immunodeficiency disorder diseases [22, 23]. Recent study reported that CXCR4 was involved in metastatic potential in osteosarcoma at bone marrow and the lungs [24]. Previous studies showed that cancer cells have higher CXCR4 expression levels compared to normal cells [25, 26].…”
Section: Introductionmentioning
confidence: 99%
“…There are always some cross-talks between different pathways in tumor occurrence and development, which provides a comprehensive understanding of tumor occurrence and development. Furthermore, the IL-8/CXCR1 axis and CXCL12/CXCR4/CXCR7 axis are commonly activated in the bone microenvironment when OS metastasis occur [ 29 , 31 , 33 , 39 , 53 ]. IL-8 and CXCL12, as the secreted molecules, are detected easily through peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, gene expression analysis showed that the focal adhesion, cytokine–cytokine receptor and extracellular matrix–receptor pathway significantly changed in MSCs compared to COS1NR cells [ 27 ]. The pathway molecules that dramatically altered were highly related to the tumor metastasis and angiogenesis such as the CXCL12/CXCR4 axis, MMP-2, and MMP-9 [ 27 , 28 , 29 ] ( Table 1 ). Some reports find that the interaction between MSCs and OS tumor cells is bidirectional ( Figure 1 ).…”
Section: Bone Microenvironment and Os Metastasismentioning
confidence: 99%